Assessment of maternal and fetal outcome in eclampsia patients getting admitted in Bundelkhand Medical College, Sagar, India on basis of general condition of patient at time of admission and induction delivery interval - Kelkar, Deepti; Naagar, Jagrati Kiran; Jain, Sheela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Eclampsia is the convulsive and most severe manifestation of the hypertensive disorders of pregnancy. Eclampsia is defined by new-onset tonic-clonic, focal, or multifocal seizures in the absence of other causative conditions. Methods: It is a prospective observational study conducted in BMC Sagar, Madhya Pradesh, India of duration one year, according to inclusion and exclusion criteria with 72 eclampsia patients. Results: Most patients had vaginal deliveries 62.5%. There were 4.2% maternal deaths. 65.4% patients’ babies were shifted to mother’s side. Lesser no. of SNCU referrals were seen in cases of LSCS as compared to vaginal deliveries, in cases where patients had GCS more than 8 at time of admission, where admission delivery interval was less than 12 hrs. Conclusions: The results of the current study indicated that better the general condition of patient at time of admission, lesser the induction/admission delivery interval-better is the fetal maternal outcome. Eclampsia could have been prevented in patients by regular antenatal visits and early detection in pre-eclampsia/gestational hypertension stage.